Multiphysics Modeling of Liver Tumor Ablation by High Intensity Focused Ultrasound (Communications in Computational Physics, 2020)
High intensity focused ultrasound is a rapidly developing technology forthe ablation of tumors. Liver cancer is one of the most common malignancies worldwide.Since liver has a large number of blood vessels, blood flow cooling can reducethe necrosed volume and may cause regeneration of the tumor to occur. All cancer cellsshould be ablated without damaging of the critical tissues. Today, treatment planningtools consider liver as a homogeneous organ. This paper is a step towards the developmentof surgical planning platform for a non-invasive HIFU tumor ablative therapy ina real liver geometry based on CT/MRI image. This task requires coupling of differentphysical fields: acoustic, thermal and hydrodynamic. These physical fields can influenceeach other. In this paper we illustrate how a computational model can be usedto improve the treatment efficiency. In large blood vessel both convective cooling andacoustic streaming can change the temperature considerably near blood vessel. Thewhole tumor ablation took only 30 seconds in the considered simulation case, which isvery small comparing with the current treatment time of several hours. Through thisstudy we are convinced that high ultrasound power and nonlinear propagation effectswith appropriate treatment planning can sufficiently reduce the treatment time.